Bartonella spp. associated with rodents in an urban protected area, Buenos Aires (Argentina). (October 2020) - De Salvo, María Nazarena; Hercolini, Carina; Arístegui, Evangelina; Bruno, Antonella; Brambati, Diego Fernando; Cicuttin, Gabriel Leonardo
Highlights: Three novel genotypes of Bartonella associated to rodents were detected. Rodents infected with these genotypes are wild species from a protected urban area. Bartonella spp. in Deltamys kempi and Scapteromys aquaticus were first reported. Abstract: At least 15 of the 30 Bartonella species are involved in human pathologies, and several of them are associated with rodents and their fleas. The aims of this study were detect and molecularly characterize the Bartonella infections in rodents from an urban protected area of ​Buenos Aires City (Argentina). A total of 186 rodents were captured and identified. For PCR of the 16S rRNA fragment, 23.7 % of the samples tested positive, and two groups (GrA and GrB) were identified. Likewise, the comparison between the sequences obtained for the gltA gene determined the presence of three genotypes, closely related to Bartonella spp. detected in sigmodontine rodents and their fleas in the Americas, which form a well-separated clade. The high prevalence of Bartonella in rodents from an urban protected area of ​Buenos Aires city is relevant from a public health perspective.